Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1017/rdc.2018.52
|View full text |Cite
|
Sign up to set email alerts
|

New AMS Dates for Verteba Cave and Stable Isotope Evidence of Human Diet in The Holocene Forest-Steppe, Ukraine

Abstract: Excavations at several locations in Verteba Cave have uncovered a large amount of human skeletal remains in association with faunal bones and Tripolye material culture. We aim to establish radiocarbon (14C) dates for eight sites and to evaluate whether these deposits are singular events, or slow accumulations over time.14C measurements, along with stable carbon and nitrogen isotope data from human and faunal remains, were collected from 18 specimens. Stable isotope values were used to evaluate human and animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…However, we are unable to treat our sample population as being deposited at or around the same time period. Although most individuals included in this study come from Site 7, which has been firmly established to date to c. 5500 calBP based on ceramics and radiocarbon dating (Nikitin et al, 2010;Ledogar et al, 2019), other chambers in the cave are not as confidently dated. For example, Chamber G3 had very few artifacts from the Tripolye culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we are unable to treat our sample population as being deposited at or around the same time period. Although most individuals included in this study come from Site 7, which has been firmly established to date to c. 5500 calBP based on ceramics and radiocarbon dating (Nikitin et al, 2010;Ledogar et al, 2019), other chambers in the cave are not as confidently dated. For example, Chamber G3 had very few artifacts from the Tripolye culture.…”
Section: Discussionmentioning
confidence: 99%
“…Most samples date to the Tripolye CII period (c. 5500 YBP) based exclusively on associated pottery found in the same cultural layer as the human remains. Nikitin et al (2010Nikitin et al ( , 2017 and Ledogar et al (2019) radiocarbon dated human and animal remains, as well as pottery sherds from Verteba, and found that the dates correspond to transitional phases in pottery decoration, with peak activity placed c. 5500 calBP, although some remains date to before or after this date. All skeletal samples excavated within VC are commingled and individual burials are difficult to identify.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a somewhat trite statement which be lies the fact that the approaches adopted by these researchers at Verteba have failed to adequately demonstrate that the remains being studied are contemporary, and as Ledogar et al (2019) clear ly demonstrate, Mesolithic through to modern cultural material and human remains are in evi dence at this location. In actual fact, and appar ently contra Madden et al (2018, p. 901), Ledogar et al (2019, p. 141) state that understanding the chronology of Verteba cave is integral to further interpretations of the material evidence from Verteba (our emphasis).…”
Section: Eneolithic Subsistencementioning
confidence: 99%
“…After World War II, archaeological excavation in Bilcze Złote was resumed in 1996-1997 (and continues to the present), by a team led by Mykhailo Sokhatskiy of the Regional Museum in Borschiv, Ukraine. The collection of artefacts from the sites is considered one of the largest assemblages of Cucuteni-Trypillia complex materials documented so far (Rook and Trela 2001;Sokhatskiy 2001a;Kadrow et al 2003;Nikitin et al 2010;Ledogar et al 2018). In addition to a large amount of human skeletal remains in association with faunal bones, it consists of thousands of potsherds, whole vessels, numerous examples of anthropo-and zoomorphic figurines, flint and stone products, and objects made of bone and antler (i.a.…”
Section: Sitementioning
confidence: 99%